2022
DOI: 10.3390/genes13061030
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of Choledochal Cyst: Insights from Genomics and Transcriptomics

Abstract: Choledochal cysts (CC) is characterized by extra- and/or intra-hepatic b\ile duct dilations. There are two main theories, “pancreaticobiliary maljunction” and “congenital stenosis of bile ducts” proposed for the pathogenesis of CC. Although family cases or CC associated with other anomalies have been reported, the molecular pathogenesis of CC is still poorly understood. Recent advances in transcriptomics and genomics analysis platforms have unveiled key expression signatures/genes/signaling pathways in the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 112 publications
(128 reference statements)
0
12
0
3
Order By: Relevance
“…More importantly, familial cases have been previously reported, including mother–daughter, father–daughter, and identical twin sisters. Despite previous reports of associated genetic variants and chromosomal abnormalities, selecting mutated genes and validating them in animal experiments remains challenging due to the multigenetic nature of CBD and the limited number of cases 8,17 . Therefore, sequencing through different modalities and analyzing more cases can help to gain insight into the complex molecular pathogenesis of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More importantly, familial cases have been previously reported, including mother–daughter, father–daughter, and identical twin sisters. Despite previous reports of associated genetic variants and chromosomal abnormalities, selecting mutated genes and validating them in animal experiments remains challenging due to the multigenetic nature of CBD and the limited number of cases 8,17 . Therefore, sequencing through different modalities and analyzing more cases can help to gain insight into the complex molecular pathogenesis of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Some surgeons have suggested that congenital biliary dilatation may consist of two disease entities, cystic and fusiform types, due to the different pathologies and operative strategies of each group 5 . Although such clinical differences have been noted, the corresponding differences in pathogenesis and molecular markers remain unclear 8,9 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, CYP7B1 is involved in the metabolism of bile acids, and loss of activity is associated with liver failure in children ( 20 ). Furthermore, Ye et al ( 21 ) reported several known genetic loci with unique functions in the development and progression of choledochal cysts and suggested that they may be caused by the combined action of multiple polymorphic genes that act independently or cooperatively. However, an association between mutations in the CYP7B1 locus and choledochal cysts has not been reported, and the relationship between them requires further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Caroli disease, commonly known as type V CC, is an autosomal recessive condition thought to be caused by ductal plate embryological distortion (11). Caroli disease is linked to biliary atresia because the pathophysiology of ductal plate deformity is similar, but it is also linked to autosomal recessive polycystic kidney disease (PKD) and, less commonly, autosomal dominant PKD (12).…”
Section: P R O V I S I O N a L L Y A C C E P T E D F O R P U B L I C ...mentioning
confidence: 99%